A Usability and User Experience Evaluation Technology for Touchable Holographic Solutions - Campos, Thiago Prado de; Damasceno, Eduardo Filgueiras; Valentim, Natasha M. C. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Touchable Holographic Solutions (THS) present novel challenges for evaluating usability and user experience (UX), particularly in relation to immersion and presence. Traditional instruments may not fully capture the specific aspects involved in interacting with holographic content. Objective: This work aims to present UUXE-ToH, a questionnaire specifically designed to evaluate usability and UX in THS contexts. Methodology or Steps: The questionnaire was developed through a multi-step process that included systematic mapping studies, exploratory search, expert validation, and studies with end users. The final version of the instrument comprises 56 items grouped into 19 UX aspects. Results: Empirical studies indicate that UUXE-ToH is a valid and reliable instrument. It identifies more usability and UX issues compared to existing instruments and is also rated more positively in terms of ease of use and acceptance.